The effects of warm and cold intrathecal bupivacaine on shivering during delivery under spinal anesthesia - Abdolreza Najafianaraki (Saudi Journal of Anaesthesia, 2012)
Background: Shivering associated with neuraxial anesthesia is a common problem that is uncomfortable for patients; it is of unknown ethnology and has no definite treatment. Purpose: The purpose of this study was to compare the effects of warm intrathecal bupivacaine stored at 23°C and cold intrathecal bupivacaine stored at 4°C on shivering during delivery under spinal anesthesia. Methods: Seventy-eight parturient women scheduled for nonemergency cesarean delivery were enrolled in the study and separated into 2 groups. The standard group received 10 mg of heavy bupivacaine 0.5% stored at room temperature (23°C) plus 10 μg of fentanyl intrathecally (warm group), and the case group received 10 mg of heavy bupivacaine 0.5% stored at 4°C plus 10 μg of fentanyl intrathecally (cold group). Data collection, including sensory block level, blood pressure, core temperature, and shivering intensity, was first performed every minute for 10 min, then every 5 min for 35 min and, finally, every 10 min until the sensory level receded to L4. Results: There were no differences between the 2 groups in the amount of bleeding, pulse rate, oxygen saturation, neonatal Apgar, and incidence of vomiting. The incidence and intensity of shivering decreased in the warm group (P=0.002). Conclusion: Warming of solutions can reduce the incidence and intensity of shivering in parturient candidates for cesarean delivery under spinal anesthesia.